Development of Predict Observe Explain (POE)-based Thematic Teaching Materials - Amalia Puspha Rini; Nunuk Suryani; Siti Sutarmi Fadhilah (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
The learning process cannot be separated from the use of teaching materials that play a role to achieve the competencies that must be achieved by the learners. The purpose of this research is to identify the developmental stages of Predict Observe Explain (POE)-based thematic teaching materials, quality, and effectiveness of teaching materials to improve the learners' learning outcomes. This is a research and development technique. The development of this product is done through the design model of ADDIE learning system, i.e. (1) analysis, (2) design, (3) development, (4) implementation, (5) and evaluation. The results show that the POE-based thematic teaching materials has excellent quality on aspects of graphics and material with the score 4,52 and score 4,75 respectively from the aspects of readability, linguistic, and presentation according to the learners as the users of the product. Furthermore, the effectiveness test results show that the average class score that does not use POE-based thematic materials is 75,72, whereas that using POE thematic materials is 82,08. Therefore, the average score in the experimental class is higher than the control one. The Sig. shows 0,010 0,05, then H0 is rejected and H1 accepted. It is concluded that there is a significant value difference between the control and experimental class.